MALIGNANT TUMOR BRENNER - Coz Carranza, Javier (2015)
For a 58 year old, operated in the E. Rebagliati Hospital of ovarian tumor, which corresponded to the pathological diagnosis of malignant Brenner tumor, which has evolved satisfactorily year after treatment is exposed. Is the comment of the issue, which because of its rarity, has seen fit to communicate.